Curative effect and technical key points of laparoscopic surgery for choledochal cysts in children - Bian, Zedong; Zhi, Yong; Zeng, Xinhao; Wang, Xiaoyong (Frontiers in Surgery, 2023)
Background and Objective: The purpose of this study was to investigate the curative effect of and experience with laparoscopic surgery for congenital choledochal cysts in children. Methods: This is a retrospective analysis of 33 children diagnosed with congenital choledochal cyst in the pediatric surgery department of the Affiliated Hospital of Southwest Medical University between January 2019 and December 2021. The cohort included 8 males and 25 females aged 0.25 to 13.7 years (median age, 3.2 years), including 21 cases of type I and 12 cases of type IV choledochal cyst (Todani classification). Laparoscopic choledochal cyst resection and hepaticojejunostomy with Roux-en-Y anastomosis were performed in all the patients. Results: Laparoscopy without transit opening was successfully performed in the 33 cases. The duration of the procedure was 235–460 min (mean ± SD, 316 ± 61 min), and intraoperative blood loss volume was 15–40 ml (23 ± 7.6 ml). Postoperative hospital stay was 7–14 days (9 ± 1.8 days). Postoperative biliary fistula and pancreatitis occurred in two cases each, and all four patients were successfully treated with conservative treatment. No anastomotic stenosis, delayed bleeding, cholangitis, intestinal obstruction, or other complications occurred. All the children were followed up for 2–36 months(median period, 17.2 months). The clinical symptoms disappeared, and no obvious hepatic dysfunction was found on abdominal color ultrasound and liver function examination. Conclusions: Laparoscopic surgery for congenital choledochal cyst in children is safe and effective, as it is a minimally invasive surgery that is associated with a low degree of trauma and bleeding, rapid postoperative recovery, and satisfactory aesthetic appearance.